The Spirit in relation to the Word, means in relation to grace - Wiarda, Timothy 1951- (2025)
If a strong working concept of the Spirit-Word relationship and the means of grace is lacking in many contemporary churches, part of the solution may be a fresh analysis and articulation of those themes. An adequate doctrine of the means of grace will reflect the complexity of the Holy Spirit's partnership with the Word, highlight the Word of God as the one essential means of grace, and throw as much light as possible on why the Word is the Spirit's necessary and perfectly suited instrument for applying redemptive grace in human lives.
Keywords: Holy Spirit; Word of God; means of grace; Ministry; Sacraments